Note on the Ptolemaic Geography of Scotland - Thomas, F W L (Proceedings of the Society of Antiquaries of Scotland, 1877)
A brief note to an error discovered in F W L Thomas' article 'Analysis of the Ptolemaic Geography of Scotland' from the Proceedings Volume 11.